Analysis of the Combination of Planting Distance and Dosage of Environmentally Friendly Liquid Organic Fertilizer on Shallot Growth - Desi Sembiring; Erni Hawayanti; Dessy Tri Astuti; Maria Lusia; Railia Karneta; Yani Purwanti; Nico Syahputra Sebayang (Politeknik Negeri Lampung., 2024)
This study aims to analyze the effect of planting distance and liquid fertilizer dosage on the growth and production of shallots (Allium ascalonicum L). This study examines the effect of a combination of planting distance and dosage of liquid organic fertilizer based on animal waste on the growth and production of shallots (Allium spp.). The study was conducted using a factorial Randomized Block Design (RAK) with two main factors, namely planting distance (D1: 20 × 20 cm, D2: 15 × 20 cm, D3: 10 × 20 cm) and dosage of liquid organic fertilizer (J0: control, J1: 250 ml/liter of water, J2: 500 ml/liter of water, J3: 750 ml/liter of water). The variables observed included plant height, number of leaves, bulb weight per plant, and bulb weight per plot. The results showed that increasing fertilizer dosage and wider planting distance significantly increased plant growth and production. ANOVA showed that planting distance and fertilizer dose had a significant effect on plant height, number of leaves, tuber weight per plant, and tuber weight per plot, but the interaction between the two factors was not significant. Application of high dose fertilizer (750 ml/liter) and wider planting distance (20 × 20 cm) resulted in optimal growth in all variables.